MIGRATORY RATIONALE OF INTER-REGIONAL FLOWS SLOVAK NATIONALS IN THE CZECH LABOR MARKET - Antonin Mikeš; Živka Deleva (European Scientific Journal, ESJ, 2014)
Gender differentiated data indicates that there is a significant gap between respondents pre and post migration. Variation in responses to a survey conducted among Slovak migrants working in the Czech Republic demonstrates that a persistent wage gap exists between genders. Individuals reflect on their decision to make a move utilizing nontraditional explanations leading the researchers to define this flow as a mixed flow involving lifestyle migration which has as secondary effect of improving the economic situation of individuals perceive a lack of opportunity in source regions.